A multi-scale micro-porous surface structure vacuum insulator and a method for manufacturing the same
Patent Information
- Application Number
- CN202311496588.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-10
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2043-11-10
AI Technical Summary
[0004]本发明的目的是解决现有的绝缘子通过表面化学改性提升绝缘子真空沿面耐压性能常面临因表面损毁而失去提升真空沿面耐压性能效果,而采用机械打磨方式构筑绝缘子表面微结构存在表面形貌不均匀、真空沿面耐压性能提升效果稳定性差的技术问题,而提供一种多尺度微孔表面结构的真空绝缘子及其制备方法
[0032] 1. This invention provides a vacuum insulator with a multi-scale microporous surface structure. The surface of the vacuum insulator is distributed with micropores of different diameters. Through the micropores of different diameters, the absorption and suppression of secondary electrons of different energies on the surface of the vacuum insulator can be achieved, so as to achieve the effect of matching the micropore diameter with the energy of the secondary electrons, thereby achieving efficient absorption of secondary electrons on the surface and significantly improving the vacuum surface withstand voltage performance.
Smart Images

Figure CN117275849B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a vacuum insulator, specifically to a vacuum insulator with a multi-scale microporous surface structure and its preparation method. Background Technology
[0002] When insulators are used in a vacuum, they inevitably encounter the problem of surface flashover. Flashover can occur even at extremely low applied voltages, causing the entire insulation system to fail in vacuum surface withstand voltage (see: Miller H C. Flashover of insulators in vacuum: the last twenty years[J]. IEEE Transactions on Dielectrics & Electrical Insulation. 2016, 22(6): 3641-3657.). Therefore, improving the vacuum surface withstand voltage performance per unit length of insulator is crucial. While increasing the size of the insulation system and the insulation distance can improve the vacuum surface withstand voltage performance of the insulator, it will result in a larger overall insulation system. Moreover, once the insulation distance exceeds a certain range, the improvement in vacuum surface withstand voltage performance becomes insignificant, meaning that there is no linear relationship between vacuum surface withstand voltage performance and insulation distance.
[0003] Since the discovery of vacuum surface flashover, researchers have conducted extensive experimental and theoretical analyses. Currently, it is generally accepted that the surface microstructure and composition of insulators are important factors affecting their vacuum surface withstand voltage performance. However, when improving the vacuum surface withstand voltage performance of insulators through surface chemical modification, there is often a risk of losing the improvement effect due to surface damage. Currently, when constructing the surface microstructure of insulators using mechanical grinding, there are problems such as uneven surface morphology and poor stability of the improvement effect on vacuum surface withstand voltage performance (see: Yamamoto O, Takuma T, Fukuda M, et al. Improving withstand voltage by roughening the surface of an insulating spacer used in vacuum[J]. IEEE Transactions on Dielectrics & Electrical Insulation. 2003, 10(4): 550-556. Zheng Nan, Yu Kaikun, Liu Guoqing, et al. Influence of surface roughness on the vacuum flashover characteristics of insulating materials[J]. New Technologies for Electrical Engineering and Energy. 2009, 28(2): 33-36.). Summary of the Invention
[0004] The purpose of this invention is to solve the technical problems that existing methods of improving the vacuum withstand voltage performance of insulators through surface chemical modification often result in the loss of the improved vacuum withstand voltage performance due to surface damage, while mechanical grinding to construct the microstructure of the insulator surface leads to uneven surface morphology and poor stability of the improvement effect on vacuum withstand voltage performance. The invention provides a vacuum insulator with a multi-scale microporous surface structure and its preparation method.
[0005] To achieve the above objectives, the present invention adopts the following technical solution:
[0006] A vacuum insulator with a multi-scale microporous surface structure, which is special in that:
[0007] It includes an insulator body and a multi-scale microporous structure located on the surface of the insulator body; the multi-scale microporous structure has micropores with different pore sizes, which are used to absorb and suppress secondary electrons of different energies when a flashover occurs.
[0008] Furthermore, the insulator body is an ABS vacuum insulator or a vacuum insulator with an ABS coating;
[0009] The multi-scale microporous structure is obtained by chemically etching ABS vacuum insulators or vacuum insulators with ABS coating; the butadiene content in ABS is 10%~30%, and the micropore diameter of the multi-scale microporous structure is 500nm~10μm.
[0010] Meanwhile, this invention provides a method for preparing a vacuum insulator with the above-mentioned multi-scale microporous surface structure, which is characterized by including the following steps:
[0011] Step 1: Prepare the insulator body;
[0012] The insulator body is an ABS vacuum insulator or a vacuum insulator with an ABS coating;
[0013] Step 2: Prepare a chromium anhydride-sulfuric acid aqueous solution with a chromium anhydride content of 100g / L~200g / L and a sulfuric acid content of 500g / L~700g / L. Place the obtained vacuum insulator into the chromium anhydride-sulfuric acid aqueous solution and etch it at 90℃~100℃ for 10min~30min to obtain the etched vacuum insulator.
[0014] Step 3: Clean the corroded vacuum insulator with deionized water and dry it to obtain a vacuum insulator with a multi-scale microporous surface structure.
[0015] Furthermore, in step 1, the butadiene content in the ABS is 10% to 30%;
[0016] In step 3, after drying, a vacuum insulator with a multi-scale microporous surface structure with a pore size distribution of 500nm~10μm is obtained.
[0017] Furthermore, in step 1, when the insulator body is an ABS vacuum insulator, the specific preparation process is as follows: using mechanical processing, the ABS insulating material is made into an ABS vacuum insulator with a preset geometric structure and size.
[0018] Furthermore, in step 1, the butadiene content in the ABS insulation material is 10%;
[0019] In step 2, a chromium anhydride-sulfuric acid aqueous solution with a chromium anhydride content of 100 g / L and a sulfuric acid content of 500 g / L is prepared and etched at 95°C for 10 min.
[0020] In step 3, after drying, a vacuum insulator with a multi-scale microporous surface structure with an average pore size of 2 μm is obtained.
[0021] Furthermore, in step 1, the butadiene content in the ABS insulation material is 30%;
[0022] In step 2, a chromium anhydride-sulfuric acid aqueous solution with a chromium anhydride content of 150 g / L and a sulfuric acid content of 600 g / L is prepared and corroded at 90°C for 30 min.
[0023] In step 3, after drying, a vacuum insulator with a multi-scale microporous surface structure with an average pore size of 7 μm is obtained.
[0024] Further, in step 1, when the insulator body is a vacuum insulator with an ABS coating, the specific preparation process is as follows: dissolve the ABS insulating material in a polar organic solvent to obtain a polar organic solution with a content of 1% to 5% ABS, then spin-coat it onto the surface of a vacuum insulator with a non-ABS insulating material, and dry it to obtain a vacuum insulator with an ABS coating.
[0025] Further, in step 1, ABS insulating material with a butadiene content of 20% is dissolved in dichloromethane to obtain a dichloromethane solution with an ABS content of 1%, which is then spin-coated onto the surface of the alumina vacuum insulator and dried to obtain an alumina vacuum insulator with an ABS coating.
[0026] In step 2, a chromium anhydride-sulfuric acid aqueous solution with a chromium anhydride content of 150 g / L and a sulfuric acid content of 600 g / L is prepared and corroded at 90°C for 20 min.
[0027] In step 3, after drying, a vacuum insulator with a multi-scale microporous surface structure with an average pore size of 4 μm is obtained.
[0028] Further, in step 1, ABS insulating material with a butadiene content of 25% is dissolved in tetrahydrofuran to obtain a tetrahydrofuran solution with a content of 5% ABS. Then, it is spin-coated onto the surface of cross-linked polystyrene vacuum insulator and dried to obtain a cross-linked polystyrene vacuum insulator with an ABS coating.
[0029] In step 2, a chromium anhydride-sulfuric acid aqueous solution with a chromium anhydride content of 200 g / L and a sulfuric acid content of 700 g / L is prepared and etched at 100°C for 25 min.
[0030] In step 3, after drying, a vacuum insulator with a multi-scale microporous surface structure with an average pore size of 5 μm is obtained.
[0031] The beneficial effects of this invention are:
[0032] 1. This invention provides a vacuum insulator with a multi-scale microporous surface structure. The surface of the vacuum insulator is distributed with micropores of different diameters. Through the micropores of different diameters, the absorption and suppression of secondary electrons of different energies on the surface of the vacuum insulator can be achieved, so as to achieve the effect of matching the micropore diameter with the energy of the secondary electrons, thereby achieving efficient absorption of secondary electrons on the surface and significantly improving the vacuum surface withstand voltage performance.
[0033] 2. In this invention, vacuum insulators with multi-scale microporous surface structures are prepared by chemically etching ABS (acrylonitrile-butadiene-styrene polymer) vacuum insulators or vacuum insulators with ABS coating. This preparation method is simple, applicable to insulators of various shapes, and under liquid phase corrosion conditions, the prepared micropores are uniformly distributed, and the stability of the vacuum surface withstand voltage improvement effect is good.
[0034] 3. The vacuum insulator with multi-scale microporous surface structure and its preparation method proposed in this invention will not damage the bulk structure of the insulator and can ensure the mechanical strength of the insulator, avoiding the risk of losing the effect of improving the vacuum surface withstand voltage performance due to surface damage. Attached Figure Description
[0035] Figure 1 This is a schematic diagram of the structure of a multi-scale microporous surface structure vacuum insulator prepared according to Embodiment 1 of the present invention;
[0036] Figure 2 This is a flowchart of a method for preparing a vacuum insulator with a multi-scale microporous surface structure according to the present invention. Detailed Implementation
[0037] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0038] The vacuum insulator proposed in this invention has a multi-scale microporous structure on its surface. This multi-scale microporous structure has micropores with different pore sizes. The micropores are matched with secondary electrons of different energies on the surface of the vacuum insulator when flashover occurs, so as to absorb and suppress secondary electrons of different energies.
[0039] Multi-scale microporous structures are obtained by chemically etching ABS vacuum insulators or vacuum insulators with ABS coatings. When the butadiene content in ABS is 10% to 30%, the pore size distribution of the multi-scale microporous structure is 500 nm to 10 μm. The higher the butadiene content, the larger the average pore size and the longer the etching time required.
[0040] Example 1
[0041] like Figure 2 As shown, a method for fabricating a vacuum insulator with a multi-scale microporous surface structure specifically includes the following steps:
[0042] Step 1: Select ABS insulation material with a butadiene content of 10%, and use mechanical processing to make the ABS insulation material into a columnar ABS vacuum insulator with a thickness of 5mm and a diameter of 30mm.
[0043] Step 2: Prepare a chromium anhydride-sulfuric acid aqueous solution with a chromium anhydride content of 100 g / L and a sulfuric acid content of 500 g / L. Place the columnar ABS vacuum insulator obtained in Step 1 into the chromium anhydride-sulfuric acid aqueous solution and etch it at 95°C for 10 min to obtain the etched ABS vacuum insulator.
[0044] Step 3: Clean the corroded ABS vacuum insulator with deionized water to remove residual chromic anhydride-sulfuric acid solution from the surface. Dry it in an oven at 80℃ to obtain a vacuum insulator with a multi-scale microporous surface structure with an average pore size of 2μm. See details below. Figure 1 This is denoted as "Multi-scale Microporous Insulator 1". (The rest of the text appears to be a fragment and requires further context for accurate translation.) Figure 1 It can be seen that the vacuum insulator surface prepared in this embodiment has a multi-scale microporous structure with uniform micropore distribution and a pore size distribution of 500nm~10μm.
[0045] Example 2
[0046] The method steps in this embodiment are the same as those in Embodiment 1, with the difference being:
[0047] In step 1, ABS insulation material with a butadiene content of 30% is selected;
[0048] In step 2, a chromium anhydride-sulfuric acid aqueous solution with a chromium anhydride content of 150 g / L and a sulfuric acid content of 600 g / L is prepared and corroded at 90°C for 30 min.
[0049] In step 3, a vacuum insulator with a multi-scale microporous surface structure and an average pore size of 7 μm is obtained, which is denoted as "multi-scale microporous insulator 2".
[0050] Example 3
[0051] Step 1: Dissolve ABS insulating material with a butadiene content of 20% in dichloromethane to obtain a dichloromethane solution with an ABS content of 1%. Then spin-coat the solution onto the surface of a columnar alumina vacuum insulator with a thickness of 10 mm and a diameter of 30 mm. After drying, a columnar alumina vacuum insulator with an ABS coating is obtained.
[0052] Step 2: Prepare a chromium anhydride-sulfuric acid aqueous solution with a chromium anhydride content of 150 g / L and a sulfuric acid content of 600 g / L. Place the columnar alumina vacuum insulator with ABS coating obtained in Step 1 into the chromium anhydride-sulfuric acid aqueous solution and etch it at 90°C for 20 min to obtain a columnar alumina vacuum insulator with ABS coating after etching.
[0053] Step 3: Clean the alumina vacuum insulator obtained in Step 2 with deionized water to remove the residual chromium anhydride-sulfuric acid aqueous solution on the surface. Dry it in an oven at 80°C to obtain a vacuum insulator with a multi-scale microporous surface structure with an average pore size of 4μm, denoted as "multi-scale microporous insulator 3".
[0054] Example 4
[0055] Step 1: Dissolve ABS insulating material with a butadiene content of 25% in tetrahydrofuran to obtain a tetrahydrofuran solution with a ABS content of 5%. Then spin-coat the solution onto the surface of a columnar cross-linked polystyrene vacuum insulator with a thickness of 5 mm and a diameter of 30 mm. After drying, a columnar cross-linked polystyrene vacuum insulator with an ABS coating is obtained.
[0056] Step 2: Prepare a chromium anhydride-sulfuric acid aqueous solution with a chromium anhydride content of 200 g / L and a sulfuric acid content of 700 g / L. Place the columnar cross-linked polystyrene vacuum insulator with ABS coating obtained in Step 1 into the chromium anhydride-sulfuric acid aqueous solution and etch it at 100°C for 25 min to obtain a columnar cross-linked polystyrene vacuum insulator with ABS coating after etching.
[0057] Step 3: Clean the cross-linked polystyrene vacuum insulator obtained in Step 2 with deionized water to remove residual chromic anhydride-sulfuric acid aqueous solution from the surface. Dry it in an oven at 80°C to obtain a vacuum insulator with a multi-scale microporous surface structure and an average pore size of 5 μm, denoted as "multi-scale microporous insulator 4". The morphology of the microporous structure of the vacuum insulators with multi-scale microporous surface structures obtained in Examples 2 to 4 is similar to... Figure 1 similar.
[0058] The vacuum insulators with multi-scale microporous surface structures prepared in Examples 1 to 4 above, along with the cylindrical insulators, were tested on a vacuum pulse surface flashover voltage test bench with a pulse width of 500 ns. The test results are shown in Table 1.
[0059] Table 1. Comparison of flashover voltage between vacuum insulators with multi-scale microporous surface structures and original insulators.
[0060]
[0061] In a vacuum environment, when high voltage induces secondary electron multiplication-induced flashover on the surface of an insulator, the energy of the generated secondary electrons is not a fixed value but exhibits a certain energy distribution. A specific energy of electron corresponds to an optimal micropore size, at which the absorption and suppression effect of electrons of that energy is optimal. As shown in Table 1, the flashover voltage of the vacuum insulators with multi-scale microporous surface structures prepared in Examples 1 to 4 is significantly improved compared to the original columnar insulator, with an improvement range of 35% to 120%. This demonstrates that the multi-scale microporous structure can effectively improve the vacuum surface withstand voltage performance of the insulator. It proves that when the vacuum insulator with the multi-scale microporous surface structure prepared by this invention is insulating in a vacuum, micropores of different sizes can capture secondary electrons of different energies, achieving a match between the micropore size and the secondary electron energy. This results in efficient absorption of surface secondary electrons, thereby suppressing the flashover process and improving the vacuum surface withstand voltage performance of the insulator.
[0062] The above description is merely a specific embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any changes or substitutions within the technical scope disclosed in the present invention should be covered within the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be determined by the scope of the claims.
Claims
1. A method for preparing a vacuum insulator with a multi-scale microporous surface structure, wherein the vacuum insulator with the multi-scale microporous surface structure comprises an insulator body and a multi-scale microporous structure located on the surface of the insulator body; the multi-scale microporous structure has micropores with different pore sizes, used to absorb and suppress secondary electrons of different energies during flashover; the multi-scale microporous structure is obtained by chemically etching an ABS vacuum insulator or a vacuum insulator with an ABS coating; the butadiene content in the ABS is 10%~30%, and the pore size of the multi-scale microporous structure is 500nm~10μm; characterized in that... Includes the following steps: Step 1: Prepare the insulator body; The insulator body is an ABS vacuum insulator or a vacuum insulator with an ABS coating; Step 2: Prepare a chromium anhydride-sulfuric acid aqueous solution with a chromium anhydride content of 100g / L~200g / L and a sulfuric acid content of 500g / L~700g / L. Place the obtained vacuum insulator into the chromium anhydride-sulfuric acid aqueous solution and etch it at 90℃~100℃ for 10min~30min to obtain the etched vacuum insulator. Step 3: Clean the etched vacuum insulator with deionized water and dry it to obtain a vacuum insulator with a multi-scale microporous surface structure.
2. The method for preparing a vacuum insulator with a multi-scale microporous surface structure according to claim 1, characterized in that: In step 1, when the insulator body is an ABS vacuum insulator, the specific preparation process is as follows: using mechanical processing, the ABS insulating material is made into an ABS vacuum insulator with a preset geometric structure and size.
3. The method for preparing a vacuum insulator with a multi-scale microporous surface structure according to claim 2, characterized in that: In step 1, butadiene accounts for 10% of the ABS insulation material; In step 2, a chromium anhydride-sulfuric acid aqueous solution with a chromium anhydride content of 100 g / L and a sulfuric acid content of 500 g / L is prepared and etched at 95°C for 10 min. In step 3, after drying, a vacuum insulator with a multi-scale microporous surface structure with an average pore size of 2 μm is obtained.
4. The method for preparing a vacuum insulator with a multi-scale microporous surface structure according to claim 2, characterized in that: In step 1, butadiene accounts for 30% of the ABS insulation material; In step 2, a chromium anhydride-sulfuric acid aqueous solution with a chromium anhydride content of 150 g / L and a sulfuric acid content of 600 g / L is prepared and corroded at 90°C for 30 min. In step 3, after drying, a vacuum insulator with a multi-scale microporous surface structure with an average pore size of 7 μm is obtained.
5. The method for preparing a vacuum insulator with a multi-scale microporous surface structure according to claim 1, characterized in that: In step 1, when the insulator body is a vacuum insulator with an ABS coating, the specific preparation process is as follows: dissolve the ABS insulating material in a polar organic solvent to obtain a polar organic solution with a content of 1% to 5% ABS, then spin-coat it onto the surface of a vacuum insulator with a non-ABS insulating material, and dry it to obtain a vacuum insulator with an ABS coating.
6. The method for preparing a vacuum insulator with a multi-scale microporous surface structure according to claim 5, characterized in that: In step 1, ABS insulating material with a butadiene content of 20% is dissolved in dichloromethane to obtain a dichloromethane solution with an ABS content of 1%, which is then spin-coated onto the surface of the alumina vacuum insulator and dried to obtain an alumina vacuum insulator with an ABS coating. In step 2, a chromium anhydride-sulfuric acid aqueous solution with a chromium anhydride content of 150 g / L and a sulfuric acid content of 600 g / L is prepared and corroded at 90°C for 20 min. In step 3, after drying, a vacuum insulator with a multi-scale microporous surface structure with an average pore size of 4 μm is obtained.
7. The method for preparing a vacuum insulator with a multi-scale microporous surface structure according to claim 5, characterized in that: In step 1, ABS insulating material with a butadiene content of 25% is dissolved in tetrahydrofuran to prepare a tetrahydrofuran solution with an ABS content of 5%. This solution is then spin-coated onto the surface of a cross-linked polystyrene vacuum insulator and dried to obtain a cross-linked polystyrene vacuum insulator with an ABS coating. In step 2, a chromium anhydride-sulfuric acid aqueous solution with a chromium anhydride content of 200 g / L and a sulfuric acid content of 700 g / L is prepared and etched at 100°C for 25 min. In step 3, after drying, a vacuum insulator with a multi-scale microporous surface structure with an average pore size of 5 μm is obtained.
Citation Information
Patent Citations
Vacuum insulator with secondary microstructure on surface and preparation method thereof
CN111180144A